Characterization Of Pyricularia Oryzae Causing Rice Blast From Rice Granary In Peninsular Malaysia - Misman, Siti Norsuha (2021)
The objectives of this study were to characterize P. oryzae isolates based on their morphological characteristics, identify P. oryzae pathotypes based on disease reaction to Malaysian Differential Varieties (MDVs), determine the genetic diversity of P. oryzae isolates based on molecular characterization and identify the virulence pattern of identified selected P. oryzae isolates (pathotypes) against specific gene for resistance harbored in the IRRI bred blast monogenic lines (IRBLs).